(untitled) (Proceedings of Voronezh State University. Series: Geology, 2021)
Introduction: Basite intrusions are important in the process of decoding the history of the formation of folded areas. Within our study we studied in detail the peculiarities of the geological structure as well as mineralogical and petrological characteristics of the Keleinogubsky massif, one of the key objects to be studied when decoding the history of the development of the Belomorian mobile belt of the Fennoscandian shield. Methodology: The parameters of metamorphism expressed in the formation of corona structures in the centre of the Keleinogubsky massif were assessed using the TWEEQU multi-equilibrium thermobarometry method in the TWQ program. The conditions of metamorphic transformations that led to the formation of new mineral parageneses on the edge of the intrusion were calculated in the NCTiFMMnASHO system using the chemical composition of the rocks (the method of pseudosections) in Perple_X. Results and discussion: Mineralogical and petrological study of the Keleinogubsky massif of the Belomorian mobile belt showed that the rocks of the intrusion had various level of preservation, from intensively metamorphised rocks of the edges to those with the preserved relicts of the primary-magmatic minerals and corona structures of the rocks in the centre of the intrusion. One of the rock-forming minerals of the massif is olivine: magmatic olivine was preserved in the rocks in the centre of the massif and along its edges and metamorphic olivine was present only in the edges of the intrusion. Both types of olivine have similar magnesium content but metamorphic olivine is different as it has higher concentrations of Mn and contains inclusions of metamorphic minerals, such as diopside, amphibole, and orthopyroxene. The assessment of the conditions of the formation of metamorphic olivine showed that its crystallisation could occur at Т 900°С and Р ≥ 8 kbar. The assessment of the conditions of metamorphic transformations in the rocks in the centre of the massif demonstrated that relict early metamorphic orthopyroxene-clinopyroxene rims around the magmatic olivine were formed at T 850–950°С and P = 3–4 kbar. Conclusions: As a result of the study of metabasites of the Keleinogubsky massif, two stages of granulite metamorphism were identified. The early metamorphic stage corresponding to the conditions of the granulite facies of low pressure (Т=850–950oС, Р=3–4 kbar) is expressed by the formation of corona structures preserved in the central part of the massif. The late granulite metamorphism of high pressure was recorded along the garnet rims of the central part of the intrusion and intensive metamorphic processing (Т=900 oС, Р ≥ 8 kbar) of the rocks of the massif edge with the formation of secondary olivine.